Enhancing Teaching Competence: Support Systems as Mediators Between Adaptability and Performance - Eligio, Lexter; Eligio, Elmer (JPAIR Multidisciplinary Research, 2026)
This study investigates the professional challenges encountered by student teachers and evaluates how their capacity for adaptability, supported by institutional frameworks, determines teaching performance. Specifically, it aims to: (1) identify the frequency and severity of classroom challenges; (2) assess the relationship between adaptability and teaching performance; and (3) examine the mediating role of support systems in strengthening teaching competence. Employing a descriptive-correlational design, data were collected from 40 student teachers at the University of Baguio during the 2024-2025 academic cycle. Structured surveys quantified classroom stressors, levels of teacher flexibility, and perceived instructional outcomes, while path analysis tested the mediation framework. Results reveal that adaptability (B = 0.760) is the strongest direct predictor of teaching success, while support systems (B = 0.429) significantly mediate this relationship, converting resilience into professional competence. Grounded in Social Cognitive Theory and Constructivism, the findings show that teaching competence emerges from the interaction of personal agency and institutional support. Beyond statistical validation, the findings highlight practical implications: mentorship, peer collaboration, and institutional resources are critical in stabilizing student teachers' performance during high-pressure instructional moments. The study's novelty lies in empirically validating a Partial Mediation Model, offering a replicable framework for teacher education research. It concludes that formalizing "adaptability scaffolding" within Teacher Education Institutions (TEIs) can enhance resilience and instructional effectiveness, contributing to more competent and adaptable educators.
Keywords: Teacher Adaptability; Teaching Performance; Support Systems; Path Analysis; Partial Mediation; Social Cognitive Theory